O kontseptsiyakh professional'nogo sporta - Solnishkin, D. V. (Teorija i Praktika fiziceskoj Kul'tury, 2001)
The definition of the amateur athlete is fixed in the Olympic Charter of the International Olympic committee. The committee forbade to the professional athletes to participate in the Olympic games down to 1988. The IOC supposes the participation in the Olympic games of professionals today. However, the Olympic Charter till now has no concept of the professional athlete. The legal regulation of the professional sports is carried outside of the IOC. Here it is possible to allocate the two basic ways of the decision of the problem: the European and the American. Since XIXth century in the USA began to occur the professional clubs on the game kinds of sports. They were united in the professional leagues later. The European approach admit the professional sports as the version of the economic activity, and the principles of its regulation are adjusted first of all by states, instead of the private persons - professional leagues.